Effects of weaning time (pm or am) on nursery-pig growth performance - C R Neill; Michael D Tokach; Joel M DeRouchey; J Ernest Minton; C N Groesbeck; K R Lawrence; C W Hastad; R O Gottlob; B M Hildabrand; T E Burkey; Jim L Nelssen; Robert D Goodband; et al. (Kansas Agricultural Experiment Station Research Reports, 2004)
An experiment was conducted to evaluate the effects of weaning time (PM or AM) on nursery-pig growth performance. The objective was to see how weanling pigs would adjust to the nursery environment if sows were removed from the farrowing crates 12 h before moving pigs into the nursery. Each sow and litter was randomly allotted to a wean time (PM or AM). Half of the litters had their sow removed on Thursday afternoon (PM), leaving the pigs in the farrowing crate. The other litters remained on the sow until weaning on Friday morning (AM). All pigs, both PM and AM treatments, were moved from the farrowing house to the nursery on Friday morning. A total of 542 weanling pigs (PIC 327L × C22) from 50 litters were used in the experiment. Pigs were approximately 21 d of age with an average initial body weight of 13.4 lb. All pigs were weighed in the farrowing house in the morning of the day that half of the sows were removed from the farrowing house that afternoon. Pigs were again weighed on d 7, 14, 21, and 28 after weaning to determine ADG, ADFI, and F/G. There was an improvement in F/G (P<0.002) from d 0 to 7 for pigs that were left on the sow until actual weaning in the AM, but this was because litters were weighed on Thursday morning and their pigs were allowed to nurse for 2 h longer than pigs in those litters whose sows were removed Thursday afternoon (PM), which caused gut loss in the pigs. Removing sows from the farrowing house early (PM) had no benefit or detrimental effect on ADG, ADFI, or F/G for the overall 28-d study.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Swine; Nursery pigs; Pigs; Wean time